Effects of prostitution: An urban population responds - Vogel, Ronald E. (American journal of criminal justice, 1986)
This article examines community perceptions about the legalization of prostitution in a large southern community. The authors utilized a random digit dialing technique to develop a representative sample consisting of 850 respondents. In addition, the authors interviewed prostitutes to determine their perceptions about how they helped individuals and society. Themes were developed from the personal accounts of the prostitutes and presented to the public to assess their feelings regarding whether or not prostitution is beneficial in certain instances. One of the major findings of the study was that 32% of the community members interviewed believed that prostitution should be legalized. This finding led the authors to discuss policy implications in the last section of the article.